2009
DOI: 10.2319/082608-452r.1
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Impact of Dental Esthetics on Quality of Life in Adolescents

Abstract: Objective: To test the hypothesis that several dimensions of the self-perceived psychosocial impacts of dental esthetics are not associated with grades of malocclusion, oral health–related quality-of-life measures, and body self-image in adolescents. Materials and Methods: This cross-sectional study included a convenience sample of 301 adolescents (mean age 16.1 ± 1.8 years, 58.1% female subjects). Demographic data were collected and dental conditions were assessed. The Dental Aesthetic Index (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
102
2
12

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(124 citation statements)
references
References 33 publications
(57 reference statements)
8
102
2
12
Order By: Relevance
“…4 The mean overall PIDAQ score was 18.1 (SD 12.3), ranging from 0 to 61. Raw distributions of scores according to PIDAQ scales are shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…4 The mean overall PIDAQ score was 18.1 (SD 12.3), ranging from 0 to 61. Raw distributions of scores according to PIDAQ scales are shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…18,23,24 The impact of oral health conditions on a person's satisfaction with their appearance might result in shame in social contacts and psychosocial disadvantage. 18,23,24 In a previous study, de Paula-Junior et al 4 showed that adolescents' self-perceived impact of dental esthetics is influenced by the severity of malocclusion, oral health-related quality of life, and body satisfaction. Multiple regression analysis revealed significant associations of independent variables (DAI, short form of the Oral Health Impact Profile, and body satisfaction scale) with the PIDAQ scale and subscales.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on this hypothesis, several studies have reported that dentofacial aesthetics play an important role in both social interaction as well as the psychosocial well-being, where the dental appearance has greater importance than when it is a measured aspect of the functional amendment itself [21] [28] [31]. Because of these findings, and the report of Shaffiula et al (2009), it is justified to argue that the quest for orthodontic treatment is influenced primarily by the desire to look attractive in search of improved self-esteem [30].…”
Section: Discussionmentioning
confidence: 99%